2019
DOI: 10.1590/1983-21252019v32n224rc
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and Productive Characteristics of Sunflower Intercropped With Forage in a Crop-Livestock Integration System

Abstract: The objective of this study was to evaluate the agronomic characteristics and yield of a sunflower crop grown together with forages in a crop-livestock integration system. The experiment was carried out in a randomized complete block design, in a 3×3 + 1 factorial scheme. Three sunflower intercropping with forage plants [sunflower + Urochloa ruziziensis (SB); sunflower + Panicum maximum cv. Tanzania (SP); sunflower + Urochloa ruziziensis + Cajanus cajan (SBGu)], sown in three ways [simultaneous sowing (SS), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(4 reference statements)
0
1
0
3
Order By: Relevance
“…O consórcio de graníferas com plantas leguminosas é uma prática que pode contribuir de forma significativa com o aporte de nitrogênio ao sistema, podendo implicar na redução da utilização de fertilizantes nitrogenados e podendo atribuir melhorias na produtividade do girassol em consórcio, conforme observado por Santos et al (2019) no estudo da produtividade do girassol em consórcio com forrageiras no sistema integração lavoura-pecuária. O diâmetro da haste (DH) é considerado uma característica importante para a cultura do girassol por estar relacionado diretamente ao acamamento.…”
Section: Resultsunclassified
“…O consórcio de graníferas com plantas leguminosas é uma prática que pode contribuir de forma significativa com o aporte de nitrogênio ao sistema, podendo implicar na redução da utilização de fertilizantes nitrogenados e podendo atribuir melhorias na produtividade do girassol em consórcio, conforme observado por Santos et al (2019) no estudo da produtividade do girassol em consórcio com forrageiras no sistema integração lavoura-pecuária. O diâmetro da haste (DH) é considerado uma característica importante para a cultura do girassol por estar relacionado diretamente ao acamamento.…”
Section: Resultsunclassified
“…No estudo de competição com forrageiras e graníferas Jakelaistis et al ( 2005) observaram que a aplicação de herbicida pós-emergente influencia no maior desenvolvimento e produtividade da cultura produtora de grãos. Fato este observado também por Santos et al (2019), trabalhando com a cultura do girassol em consórcio dos forrageiras.…”
Section: Resultsunclassified
“…Souza et al (2019), using different macrophyte species, also observed increases in sunflower plant growth variables, especially with Salvinia auriculata at 150% nitrogen recommendation (NR). Santos et al (2019) state that stem diameter is an important characteristic for sunflower culture, as chapters with larger diameters are indicative of larger number of hairs. It can be an indicator of development and productivity for sunflower plants (DALCHIAVON et al, 2016).…”
Section: Resultsmentioning
confidence: 99%